Persepsi dan Partisipasi Masyarakat dalam Melestarikan Bekantan dan Habitatnya di Samboja, Kalimantan Timur - Syamsu Eka Rinaldi; Tri Atmoko; Mukhlisi Mukhlisi (Program of Biology Education, Universitas Lambung Mangkurat, 2021)
The Kuala Samboja River is one of the proboscis monkey habitats outside the conservation area in Samboja District, Kutai Kartanegara Regency. This study aims to determine the perception and level of public participation in the conservation of proboscis monkeys and their habitat. The research was conducted using the interview method using a questionnaire. Respondents were selected using the purposive sampling method using the Slovin sample size. The validation of the questionnaire used product moment correlation analysis (r), while the reliability test used the Cronbach's (α) method. Data were analyzed by Likert scale and scoring. The results showed that the level of public perception of the conservation of proboscis monkeys and their habitat was classified as very agree (mean score: 223.5), while the level of desire to participate was quite active (mean score: 198.5). Based on the results of the study, it is known that the community gives a good perception of proboscis monkey conservation. Meanwhile, the level of community participation is still moderate. Socialization needs to be directed at increasing community participation to be more active in conserving proboscis monkeys and their habitat.